Outcomes after transperitoneal laparoscopic ureteronephrectomy for the treatment of primary renal neoplasia in seven dogs. (7th July 2021) - Hart, Edward; Singh, Ameet; Thomson, Christopher B.; Appleby, Ryan; Richardson, Danielle; Hocker, Samuel; Bernard, Sarah; Pinard, Christopher
Abstract: Objective: To describe the perioperative characteristics and outcomes in dogs that underwent transperitoneal laparoscopic ureteronephrectomy (TLU) for primary renal neoplasia. Study design: Short case series. Animals: Seven client‐owned dogs. Methods: Medical records were reviewed and data extracted regarding perioperative characteristics and animal outcomes. TLU was performed using a single‐port + 1 or multiple port techniques. Hemostatic clips or a vessel‐sealing device were used for occlusion of renal hilar vessels. The ureter was occluded and transected close to the ureterovesicular junction and the tumor was placed in a specimen retrieval bag for extraction from the abdomen. Results: Preoperative contrast enhanced computed tomography (CECT) was performed in 6/7 dogs. Median estimated tumor volume measured from abdominal CECT removed by TLU was 32.42 cm 3 (interquartile range [IQR] 14.76–94.85). Median surgery time for TLU was 90 minutes (IQR 85–105). In one dog, elective conversion to open laparotomy was performed due to large tumor size. Median time to discharge was 31 hours (IQR 24–48). No major perioperative complications occurred and all dogs survived to discharge. Progression free survival in four dogs was 422 days (IQR 119–784). Conclusion: TLU was performed for the extirpation of modest sized primary renal tumors with acceptable perioperative outcomes and a low complication rate. Clinical relevance: TLU may be considered for the treatment of selected cases of primary renal neoplasia in dogs.